Issues of oppression in family relationships. - Tovbaeva, Muqaddam Safarovna (International Journal of Psychosocial Rehabilitation, 2020)
The article deals with the psychological effects of domestic violence, intimidation, coercion, humiliation, abuse, violence, attempted evictions, beatings of children, leaving them helpless or submissive. information is given. According to the author, it is expedient to study scientifically and practically the causal conditions, classification, and behavioral characteristics of factors such as infliction of various degrees of bodily injury, oppression, beatings, torture, and severe harm as a result of domestic violence.